Autoimmune septin-5 cerebellar ataxia. Issue 5 (September 2018) - Honorat, Josephe A.; Lopez-Chiriboga, A. Sebastian; Kryzer, Thomas J.; Fryer, James P.; Devine, Michelle; Flores, Angela; Lennon, Vanda A.; Pittock, Sean J.; McKeon, Andrew
Abstract : Objective: To report a form of autoimmune cerebellar ataxia in which antibodies target septin-5, a guanosine triphosphate (GTP)-binding neural protein involved in neurotransmitter exocytosis. Methods: Archived sera and CSF specimens with unclassified synaptic antibodies were re-evaluated by tissue-based indirect immunofluorescence assay. Autoantigens were identified by Western blot and mass spectrometry. Recombinant protein assays (Western blot, cell based, and protein screening array) confirmed antigen specificity. Results: Serum and CSF from 6 patients produced identical synaptic immunoglobulin G (IgG) staining patterns of synaptic regions (neuropil) of the mouse cerebrum and cerebellum. The molecular layer of the cerebellum and the thalamus demonstrated stronger immunoreactivity than the midbrain, hippocampus, cortex, and basal ganglia. The antigen revealed by mass spectrometry analysis of immunoprecipitated cerebellar proteins and confirmed by recombinant protein assays was septin-5. All 4 patients with records available had subacute onset of cerebellar ataxia with prominent eye movement symptoms (oscillopsia or vertigo). None had cancer detected. Improvements occurred after immunotherapies (2) or spontaneously (1). One patient died. Conclusion: Septin-5 IgG represents a biomarker for a potentially fatal but treatable autoimmune ataxia.